Biomolecular interaction and in vitro cytotoxicity of ruthenium complexes containing heterocyclic hydrazone. Is methanol a non-innocent solvent to influence the oxidation state of the metal and ligation of hydrazone?. (16th August 2017) - Jayanthi, Eswaran; Venkataramana, Mudili; Neethu, Sankar; Bhuvanesh, N.S.P.; Dharmaraj, Nallasamy
Graphical abstract: A new set of ruthenium(III) hydrazone complexes have been reported with their crystal structures. Their biomolecular interaction studies with DNA/BSA indicated a strong interaction. In vitro cytotoxicity analyses done with human breast cancer cell models (MCF-7 and MDAMB-453) established the anticancer potential of these complexes. Abstract: Two new stable ruthenium complexes, [Ru III (HL)Cl2 (PPh3 )2 ] (1 ) and [Ru II (L)(CO)(PPh3 )2 ] (2 ), were synthesized from the reaction of [Ru III Cl3 (PPh3 )3 ] with thiophene-2-carboxylic acid (2-hydroxyl-benzylidene)-hydrazide (H2 L ) in chloroform–methanol. Surprisingly, the same reaction performed by adding KOH to the reaction medium resulted in the exclusive formation of the bivalent ruthenium carbonyl complex2 . Both complexes1 and2 were characterized by elemental analysis, EPR/NMR and single crystal X-ray diffraction study. From the DNA binding and quenching experiments, an intercalative mode of binding with DNA was identified. The DNA cleavage activity of the complexes, monitored using gel electrophoresis, showed significant damage of the plasmid DNA. Bovine serum albumin (BSA) binding capabilities analysed using absorption and emission spectroscopic methods showed a strong binding interaction of complexes1 and2 with BSA. The in vitro cytotoxicity studied against human breast cancer cell models (MCF-7 and MDAMB-453) showed that complex1 possessed activity comparable to that of the standard positive reference cisplatin. The IC50 concentration of complexes treated with cancer cell models exhibited a significant increase in lactate dehydrogenase release and nitrite content in the culture medium. Overall, the trivalent ruthenium hydrazone complex1 exhibited better activity towards biomolecules and cancer cells than complex2 .